Total protein composition of young and adult Biomphalaria alexandrina snails with different compatibilities to Schistosoma mansoni infection - Sadaka, Hayam A; Abou-El-Naga, Iman Fathy; Amer, Eglal I; Diab, Iman H; Kher, Safaa I (Revista de Biología Tropical, 2016)
In the current study differentiation of the total proteins among Biomphalaria alexandrina snails at different ages was done to identify the proteins responsible for the snails’ compatibility outcome. The work was conducted on snails that differ in their age and the genetic backgrounds. Four subgroups from the progeny of self reproduced susceptible and resistant snails were studies. Infection rates of these subgroups (young susceptible, adult susceptible, young resistant and adult resistant) were 90%, 75%, 40% and 0% respectively. Using Sodium dodecyl sulphate polyacrylamide gel electrophoresis, differences in protein expression were shown between adult and young snails in different subgroups. Dice similarity coefficient was calculated to determine percentage band sharing among the experimental subgroups. The results revealed that the combination of similarities between both age and compatibility status of the snails has led to the highest similarity coefficient followed by the combination of similarities of both genetic origin and age although they differ in the compatibility status. On the other hand, the differences in the genetic background, age and compatibility status have led to the least similarity index. It was also found that in young snails the genetic background plays the main role in determination of their compatibility, while the internal defense system has the upper hand in determination of adult compatibility. Further characterization of the shared protein bands among the studied subgroups is needed to clarify their role in host-parasite relationship.